Psoriasis Induced by Trastuzumab (Herceptin®) - Kim, Dae Hun (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2013)
Trastuzumab (Herceptin), a humanized monoclonal antibody, is a cancer drug developed to target the human epidermal receptor (HER) 2, which is overexpressed in some cancer cells. Cutaneous side effects, such as folliculitis, xerosis, and alopecia have not been reported with therapies targeting HER2, in spite of the frequent observances of such with the therapies targeting the epidermal growth factor receptor. We experienced a patient in whom psoriasis was triggered by the trastuzumab treatment for breast cancer. She was a 57-year-old woman with erythematous and scaly plaques occurring a few months after starting trastuzumab, with repeated aggravation after the re-administration of trastuzumab for the breast cancer. Histologic examination showed the typical features of psoriasis with parakeratosis, epidermal hyperplasia, elongation of the rete ridges, and a lymphocytic and polymorphonuclear cell infiltrate in the dermis. To the best of our knowledge, this is the first report of psoriasis triggered by trastuzumab treatment for breast cancer.